2022
DOI: 10.3390/microorganisms10112203
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri MJM60668 Prevent Progression of Non-Alcoholic Fatty Liver Disease through Anti-Adipogenesis and Anti-Inflammatory Pathway

Abstract: Non-alcoholic fatty liver disease (NALFD) is a disease characterized by liver steatosis. The liver is a key organ involved in the metabolism of fat, protein, and carbohydrate, enzyme activation, and storage of glycogen, which is closely related to the intestine by the bidirectional relation of the gut-liver axis. Abnormal intestinal microbiota composition can affect energy metabolism and lipogenesis. In this experiment, we investigated the beneficial effect of Lactobacillus reuteri MJM60668 on lipid metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 90 publications
1
2
0
Order By: Relevance
“…It has been suggested that the cholesterol-lowering effects of L. reuteri NCIMB 30242 may be couple to its capability of decoupling bile acids without having any impact on triglyceride levels. Reduction of only triglycerides and not on cholesterol may suggest a strain specific effect on lipid metabolism more in line with findings in other L. reuteri strains [ 37 ]. Interestingly, Dixon et al presented a systematic review on the efficacy of probiotics showing that statistically significant changes were seen in improvements of blood-pressure, cholesterol, LDL and HDL, however no significant change was observed in the outcome of triglycerides [ 38 ].…”
Section: Discussionsupporting
confidence: 78%
“…It has been suggested that the cholesterol-lowering effects of L. reuteri NCIMB 30242 may be couple to its capability of decoupling bile acids without having any impact on triglyceride levels. Reduction of only triglycerides and not on cholesterol may suggest a strain specific effect on lipid metabolism more in line with findings in other L. reuteri strains [ 37 ]. Interestingly, Dixon et al presented a systematic review on the efficacy of probiotics showing that statistically significant changes were seen in improvements of blood-pressure, cholesterol, LDL and HDL, however no significant change was observed in the outcome of triglycerides [ 38 ].…”
Section: Discussionsupporting
confidence: 78%
“…Thus, supplementation with probiotics has resulted in the improvement of these inflammatory parameters close to the normal levels. A significant decrease in circulating endotoxin and pro-inflammatory cytokines-IL-1β, IL-6 and TNF-α-as well as an increase in the anti-inflammatory IL-10 have also been observed after probiotic administration [65,72,78]. Moreover, it has been evidenced that probiotic supplementation is capable of downregulating the toll-like receptor (TLR)4 and TLR9-induced inflammatory responses, as well as decreasing the expression of NLRP3 (NLR family pyrin domain containing 3) and ASC (apoptosis-associated speck-like protein containing a CARD), suggesting a regulation in the expression of the NLRP3 inflammasome [79].…”
Section: Probiotics and Animal Modelsmentioning
confidence: 98%
“…Inflammation was suppressed by L. reuteri MJM60668 , which inhibits lipogenesis, enhances fatty acid oxidation, and inhibits lipogenesis. [ 40 ] Xin et al. found that L. johnsonii BS15 positively affects liver lipid peroxidation through an anti‐oxidative stress enhancement of liver antioxidant defenses.…”
Section: Discussionmentioning
confidence: 99%